2013
DOI: 10.3171/2013.8.spine12948
|View full text |Cite
|
Sign up to set email alerts
|

Primary surgical management by reduction and fixation of unstable hangman's fractures with discoligamentous instability or combined fractures

Abstract: Object Several controversial issues arise in the management of unstable hangman's fractures. Some surgeons perform external reduction and immobilize the patient's neck in a halo vest, while others perform surgical reduction and internal fixation. The nonsurgical treatments with rigid collar or halo vest immobilization present problems, including nonunion, pseudarthrosis, skull fracture, and scalp laceration and may also fail to achieve anatomical realignment of the local C2–3 kyphosis. With recent advances in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…15 On the contrary, Shin et al described posterior reduction and screw fixation as a primary treatment strategy in all patients with hangman's fracture of all grades. 19 It was previously reported that stable fractures (L-E Type I) and certain adequately reduced L-E Type II fractures are generally treated with brace therapy involving a rigid cervical collar or halo immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…15 On the contrary, Shin et al described posterior reduction and screw fixation as a primary treatment strategy in all patients with hangman's fracture of all grades. 19 It was previously reported that stable fractures (L-E Type I) and certain adequately reduced L-E Type II fractures are generally treated with brace therapy involving a rigid cervical collar or halo immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…20,23 A recent paper by Shin et al advocates for the early use of surgical fixation of hangman's fractures because of high rates of nonunion and pseudarthrosis, along with patient dissatisfaction associated with long-term rigid cervical collar and halo use. 27 Shin et al suggested the use of posterior reduction and screw fixation as a primary treatment for hangman's fractures of all grades. As such, surgical stabilization, including minimally invasive direct percutaneous fracture fixation, is a potentially useful adjunct in the proper management algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Although we still recommend nonoperative management when possible, Shin et al have advocated for the use of early surgical intervention. 27 If patients are carefully selected and intraoperative neuronavigation is used, this technique seems to be a safe and effective method for the treatment of traumatic spondylolisthesis of the axis.…”
Section: Discussionmentioning
confidence: 99%
“…3,8,13,15,[17][18][19]21,23,25,28,31,33,34 Posterior surgery was previously performed using C1-3 wire fixation, but this technique requires postoperative halo vest immobilization and sacrifices atlantoaxial function. 13 Bristol et al 3 treated the atlantoaxial isthmus fracture by direct screw fixation to retain atlantoaxial function.…”
mentioning
confidence: 99%